Differential potassium uptake and utilization efficiency of oil palm (Elaeis guineensis Jacq.) commercial cultivars - Sim, Choon Cheak (2017)
Conventional approaches of using higher fertilizer inputs to sustain profitable yields in oil palm plantations can be uneconomical and produce inconsistent results. In addition, the biological potential of attaining much higher oil yield is often limited by marginal environments. Nutrient efficient genotypes could potentially lead to higher productivity when grown on marginal land and eventually improve the sustainable use of resources and production of palm oil. Studies on interaction effects between planting material and nutrient inputs show differential uptake and utilization efficiency between the commercially available oil palm planting materials. The differences in leaf nutrient contents between genotypes and yield response to K fertilizer inputs demonstrated the presence of more efficient uptake characteristics. If such potassium efficient cultivars could be widely adopted, the industry would not only be capable of saving resources but also to increase productivity as well. Potassium use in palm oil production ranges from approximately 13 to 21 kg of palm oil per kg of potassium with varying degree of efficiency depending on planting varieties. The potassium use efficiency could potentially increase by 50 % in the most potassium efficient cultivar. The objectives of this study were (1.) to evaluate the growth response of selected oil palm crosses under K deficient environment and (2.) to estimate potassium use efficiency of different oil palm genotypes as part of the effort to elucidate the physiological mechanism potassiumefficient oil palms. Phenotypic responses of 5 oil palm genotypes with genetic origin from Deli and Nigerian Dura interbred with AVROS, Nigerian and Yangambi Pisiferas grown under deficient and adequate potassium supplies were evaluated. Potassiumefficient genotypes were differentiated in this experiment, where the potassium-efficient genotypes produced higher biomass (by 37.3 %) and had higher potassium uptake activity (by 41.7 %). The efficient genotypes were capable of extracting higher amount of soil potassium (by 95 %) under deficient potassium supplies. The K-efficient genotype was capable of sustain growth and to adapt to potassium-deficient environments. Alterations in rooting behaviour (increasing fine root proliferation) and maintenance of shoot growth (frond production rate) are the primary physical traits of adaptation to potassium-deficient environment. The ability to remobilize the limiting nutrients from sink tissues to source tissues i.e. from the bole and rachis to the pinnae (the photosynthetically active tissues) and roots (to search for more nutrients allows the plant to further acquire more resources to ensure continuous growth) is also a key trait. Comparative analysis of transcriptomic differences between the efficient and in-efficient genotypes showed significant upregulation of potassium transporters (KUP3, KUP8 and KUP11) in the roots of the K-efficient genotype and genes which confer tolerance to stress, minimizes cellular damage, stress regulation and potassium homeostasis. Traits for potassium efficiency are conferred by the interaction of multiple complex mechanisms, governed by pool of genes controlling the physiological processes of stress regulation, cellular development and metabolite homeostasis. Stress detection and regulating cellular processes to mitigate the effect of stress could be the key in first tolerating and reducing damages to cellular and consequently enhancing the genotype’s ability to adapt, absorb and utilize nutrients more effectively.